Different wavelengths light to induce physiological changes callus for the biosynthesis of gymnemic acid in Gymnema sylvestre - Ahmed, A.B.A.; Rao, A.S.; Rao, M.V.; Taha, R.M. (2012)
A callus culture of Gymnema sylvestre was cultivated under different light conditions (blue, white, red and green light). Green-white coloured gymnemic acid containing cell groups were formed on the surface of the callus culture under blue light respectively. The phytohormone kinetin enhanced the gymnemic acid formation in blue light, but was unable to induce gymnemic acid in darkness. The phytohormone 2,4-D induced the formation gymnemic acid under all light conditions studied. Analysis of the callus growth phase under all treatments revealed that gymnemic acid accumulation was maximum (12.22 mg/g d.w) in the callus during stationary phase of 45 days, grown in MS medium with 2,4-D (1.5 mg/l) and KN 0.5 mg/l under white fluorescent light. Blue light enhanced the gymnemic acid accumulation up to 4.4 fold of that found under white fluorescent light and 2.8 fold of that found in intact leaves. Present findings concluded that blue light can be used as tool for enhancing pentacyclic tri-terpenoids in batch culture of G. sylvestre.